UJI OPTIMALISASI DAYA HAMBAT EKSTRAK DAUN TEH HIJAU (Camellia Sinensis) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli DAN Staphylococcus aureus - HD. Widya , Salsyabillah Ramadhani; Diah Titik , Mutiarawati; Suliati, Suliati (Analis Kesehatan Sains, 2021)
Research on substances as new antibiotics to inhibit or kill bacteria that are resistant to antibiotics needs to be done. One of the simplicia has an antibacterial effect is the leaves of green tea (Camellia sinensis). Antibacterial content the leaves of green tea (Camellia sinensis), namely alkaloids, saponins, tannins, and catechins (polyphenols). Tea one of the favorite products from Indonesia’ estate. The purpose of this study was to determine optimization of the inhibitory power the leaves of green tea’s (Camellia sinensis) extract against the growth of Escherichia coli and Staphylococcus aureus. This research is an experimental laboratory conducted at Bacteriology”s Laboratory, Department of Medical Laboratory Technology Surabaya in November 2020 - April 2021. This study uses the Kirby Bauer disk diffusion method, namely Mueller Hinton Agar (MHA) media which has been planted with Escherichia coli and Staphylococcus aureus with disks that have been prepared. soaked in the leaves of green tea’s (Camellia sinensis) extract at concentrations of 25%, 50%, 75%, and 100% and then incubated for 24 hours in an incubator. The results can be concluded the leaves of green tea’s (Camellia sinensis) extract can be used as an antibacterial. Optimal of results in this research were Escherichia coli at a concentration of 25% with an average diameter of 10,25 mm and Staphylococcus aureus at a concentration of 100% with an average of 22,5 mm. This is because content the leaves of green tea’s (Camellia sinensis) is catechins and alkaloids as strong antibacterials